The constitution of ethics: the ethics of the market and its critique - Hinkelammert, Franz J. (2021)
The paper proposes an analysis of the market and the ethics of the market based on its own operation. It focuses on the basic rules of this ethic: you will not kill, you will not steal and you will not cheat to appropriate the property of others. I analyze the subject first in Plato, then in modern authors such as Adam Smith, Immanuel Kant, Max Weber and Ludwig Wittgenstein. We end the article with a discussion of the needs, the option for life, and the life-death judgments in Spinoza and Marx.